Modification of Collagen for Biomedical Applications: A Review of Physical and Chemical Methods - Yu, Xiaoyue; Tang, Cuie; Xiong, Shanbai; Yuan, Qijuan; Gu, Zhipeng; Li, Zhen; Hu, Yang (Current Organic Chemistry, 2016)
Collagen, the most abundant structural protein in mammals, has drawn attention of the scientists in biomedical science to a large extent. Although collagen and collagenous materials are famous for the excellent biological properties (good bioactivity, biodegradability, biocompatibility and lower immunogenicity), they still always suffer from the limitation by the relatively weak mechanical property, chemical stability and resistance to enzymatic degradation. This paper focuses to review the various physical and chemical methods that have been reported to enhance the physicochemical property of collagen and collagenous materials in biomedical applications. The effect of modification on collagen largely depends on the reaction sites and the types of chemical bonds. Modification methods divided into physical and chemical types are discussed in detail in the present review, focusing on both the physicochemical property and the biological property.
Keywords: biomedical applications